Distinct Copy Number, Coding Sequence, and Locus Methylation Patterns Underlie Rhg1-Mediated Soybean Resistance to Soybean Cyst Nematode. Issue 2 (14th April 2014) - Cook, David E.; Bayless, Adam M.; Wang, Kai; Guo, Xiaoli; Song, Qijian; Jiang, Jiming; Bent, Andrew F.
Abstract : A multiple-gene locus in soybean conferring disease resistance has evolved three locus types defined by copy number, protein coding, expression, and DNA methylation differences . Abstract: Copy number variation of kilobase-scale genomic DNA segments, beyond presence/absence polymorphisms, can be an important driver of adaptive traits. Resistance to Heterodera glycines ( Rhg1 ) is a widely utilized quantitative trait locus that makes the strongest known contribution to resistance against soybean cyst nematode (SCN ), Heterodera glycines, the most damaging pathogen of soybean ( Glycine max ). Rhg1 was recently discovered to be a complex locus at which resistance-conferring haplotypes carry up to 10 tandem repeat copies of a 31-kb DNA segment, and three disparate genes present on each repeat contribute to SCN resistance. Here, we use whole-genome sequencing, fiber-FISH (fluorescence in situ hybridization), and other methods to discover the genetic variation at Rhg1 across 41 diverse soybean accessions. Based on copy number variation, transcript abundance, nucleic acid polymorphisms, and differentially methylated DNA regions, we find that SCN resistance is associated with multicopy Rhg1 haplotypes that form two distinct groups. The tested high-copy-number Rhg1 accessions, including plant introduction (PI) 88788, contain a flexible number of copies (seven to 10) of the 31-kb Rhg1 repeat. The identified low-copy-number Rhg1 group, including PI 548402 (Peking) and PI 437654, contains three copies of the Rhg1 repeat and a newly identified allele of Glyma18g02590 (a predicted α-SNAP [α-soluble N -ethylmaleimide–sensitive factor attachment protein]). There is strong evidence for a shared origin of the two resistance-conferring multicopy Rhg1 groups and subsequent independent evolution. Differentially methylated DNA regions also were identified within Rhg1 that correlate with SCN resistance. These data provide insights into copy number variation of multigene segments, using as the example a disease resistance trait of high economic importance.